2011
DOI: 10.1016/j.molcel.2011.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Fluorescence Measurements of Ribosomal Translocation Dynamics

Abstract: We employ single-molecule fluorescence resonance energy transfer (smFRET) to study structural dynamics over the first two elongation cycles of protein synthesis, using ribosomes containing either Cy3-labeled ribosomal protein L11 and A- or P-site Cy5-labeled tRNA or Cy3 and Cy5 labeled tRNAs. Pre-translocation (PRE) complexes demonstrate fluctuations between classical and hybrid forms, with concerted motions of tRNAs away from L11 and from each other when classical complex converts to hybrid complex. EF-G·GTP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
220
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(245 citation statements)
references
References 58 publications
25
220
0
Order By: Relevance
“…As determined from both fluorescence change and puromycin reactivity measurements, an EF4/EF-G ratio of 0.1-0.2 suffices to achieve half conversion of PRE complex to X 3 , suggesting an apparent affinity of EF4 for PRE complex that is some 5-10 times higher than that of EF-G. Single molecule FRET (smFRET) studies have shown that PRE complexes are distributed between hybrid and classical states (2,3) and that a fraction of these complexes fluctuate between these states (2,22). Following Chen et al (22), we used smFRET to examine PRE complexes formed using two different sets of fluorescently labeled materials.…”
Section: Ef4mentioning
confidence: 99%
See 1 more Smart Citation
“…As determined from both fluorescence change and puromycin reactivity measurements, an EF4/EF-G ratio of 0.1-0.2 suffices to achieve half conversion of PRE complex to X 3 , suggesting an apparent affinity of EF4 for PRE complex that is some 5-10 times higher than that of EF-G. Single molecule FRET (smFRET) studies have shown that PRE complexes are distributed between hybrid and classical states (2,3) and that a fraction of these complexes fluctuate between these states (2,22). Following Chen et al (22), we used smFRET to examine PRE complexes formed using two different sets of fluorescently labeled materials.…”
Section: Ef4mentioning
confidence: 99%
“…Single molecule FRET (smFRET) studies have shown that PRE complexes are distributed between hybrid and classical states (2,3) and that a fraction of these complexes fluctuate between these states (2,22). Following Chen et al (22), we used smFRET to examine PRE complexes formed using two different sets of fluorescently labeled materials. PRE-Lt complex contains L11 labeled with Cy3 at position 87 (L11 Cy3 ) and fMetPhe-tRNA Phe (Cy5) in the A site and unlabeled tRNA fMet in the P site.…”
Section: Ef4mentioning
confidence: 99%
“…Elongation factor 2 in complex with GTP binds to the PRE ribosome and, regardless of its initial conformation, causes an appearance of the hybrid tRNA states (5,10). After binding, the protein undergoes conformational changes that bring the second superdomain into the A-site of the SSU (11,12), where it interacts via domain IV with the decoding centre and tRNA-mRNA-complex (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Attaching two differently coloured dyes to a system of interest also allows single-molecule Förster (fluorescence) resonance energy transfer (smFRET) to be measured 12 . This approach facilitates the real-time measurement of dye-to-dye distances of up to ~5 nm.…”
Section: Techniques For In Vitro Single-molecule Analysismentioning
confidence: 99%